2009
DOI: 10.1002/cbic.200900122
|View full text |Cite
|
Sign up to set email alerts
|

Identification of OxyE as an Ancillary Oxygenase during Tetracycline Biosynthesis

Abstract: The double hydroxylation of 6-pretetramid to 4-keto-anhydrotetracycline is a key tailoring reaction during the biosynthesis of the broad-spectrum antibiotic tetracyclines. It has been shown previously by heterologous reconstitution that OxyL is a dioxygenase and is the only enzyme required to catalyze the insertion of oxygen atoms at the C-12a and C-4 positions. We report here that OxyE, a flavin adenine dinucleotide (FAD)-dependent hydroxylase homologue, is an ancillary mono-oxygenase for OxyL during oxytetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
2
22
0
1
Order By: Relevance
“…The potential quinone-forming activities of OxyG homologs led to initial speculation that it may be involved in the formation of 17; however, as described above, OxyL (with the help of OxyE) has been shown to be sufficient for catalysis of this step. This does not eliminate, however, the possibility of an auxiliary role of OxyG such as that shown for OxyE (64). An interesting aspect of the C5 hydroxylation is that because it is a step unique to OTC biosynthesis, one would expect the gene responsible to be absent from the CTC gene cluster, much as the CTC C7 halogenase (73) is absent from the OTC gene cluster.…”
Section: Formation Of Otcmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential quinone-forming activities of OxyG homologs led to initial speculation that it may be involved in the formation of 17; however, as described above, OxyL (with the help of OxyE) has been shown to be sufficient for catalysis of this step. This does not eliminate, however, the possibility of an auxiliary role of OxyG such as that shown for OxyE (64). An interesting aspect of the C5 hydroxylation is that because it is a step unique to OTC biosynthesis, one would expect the gene responsible to be absent from the CTC gene cluster, much as the CTC C7 halogenase (73) is absent from the OTC gene cluster.…”
Section: Formation Of Otcmentioning
confidence: 99%
“…The hydroxylation activities of OxyL were confirmed in vitro, as addition of purified OxyL to 13 produced a short-lived product identified as 17. A subsequent report by Wang et al (64) indicated that OxyE, another FAD-dependent oxygenase, is a C4 hydroxylase and plays an ancillary role in this key dihydroxylation step that converts 13 to 17. Although OxyL can perform the dihydroxylation of C12a and C4 alone, the presence of OxyE significantly increases the titer of OTC, likely by increasing the rate of this key tailoring step (Fig.…”
Section: Formation Of Anhydrotetracyclinementioning
confidence: 99%
“…However, during th e last decade, the most signifi cant insight into OTC biosynthesis has been gained by Tang´s research group at the University of California, Los Angeles (USA) (57)(58)(59)(60)(61)(62)(63).…”
Section: Biosynthetic Pathway Of Tetracycline Antibioticsmentioning
confidence: 99%
“…The C6 methylation is probably followed by a double hydroxylation of ring A at C4/C12a by oxygenase pairs OxyL in OxyE, whereas OxyE is believed to be an ancillary monooxygenase for OxyL with a nonessential but important role in improving its catalytic effi ciency as a C4 hydroxylase (7 and 8 in Fig. 4b) (60). Hydroxylation at C4 is a prerequisite for the incorporation of an amino group at C4 by PLP-dependent aminotransferase OxyQ (9 in Fig.…”
Section: Tailoring Reactions Of the Basic Tetracycline Backbonementioning
confidence: 99%
“…hydroxylase (Wang et al, 2009). In contrast to OTC, CHD does not contain hydroxyl groups at C-5 and C-6 and differs in the pattern of reduction of carboxyl groups at C-11 and C-12, thus resulting in the less polar structure of CHD (Fig.…”
mentioning
confidence: 99%